2013
DOI: 10.1073/pnas.1321205110
|View full text |Cite
|
Sign up to set email alerts
|

Osmosensory signaling in Mycobacterium tuberculosis mediated by a eukaryotic-like Ser/Thr protein kinase

Abstract: Significance Osmotic stress is one of many environmental hazards encountered by bacteria during the course of infection, but our understanding of how bacteria perceive and respond to changes in extracellular osmolarity is still incomplete. We show that Mycobacterium tuberculosis , the pathogen that causes tuberculosis in humans, responds, in part, through an osmosensory pathway regulated by the Ser/Thr protein kinase (STPK) PknD. Our work demonstrates that increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 81 publications
4
59
0
Order By: Relevance
“…8). In contrast, PknD, which contains a ␤-propeller ECD, not only senses osmolarity but also is positioned in the network to regulate the stressosome in response to upstream STPKs (17,22,49).…”
Section: Discussionmentioning
confidence: 99%
“…8). In contrast, PknD, which contains a ␤-propeller ECD, not only senses osmolarity but also is positioned in the network to regulate the stressosome in response to upstream STPKs (17,22,49).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria typically counteract such fluctuations through the compensatory accumulation or expulsion of compatible solutes that restore osmotic balance in the cells. In addition, pathogenic bacteria have virulenceassociated osmosensory mechanisms that are triggered at the transcriptional level [13,14]. It can be conclude that increasing sodium chloride concentration could decrease viability of cells and cell division patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Although the members in Mycobacterium genus are acid fast bacteria having a rigid complex cell wall, but it seems they cannot face to increasing osmotic pressure by synthesis of compatible solutes. Recently, Hatzios et al 2013. reported that osmotic stress stimulates a signaling network in Mycobacterium tuberculosis regulated by the eukaryotic-like receptor PknD (Ser /Thr protein kinase) [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During cell wall synthesis, PknD positively regulates the transport of phthiocerol dimycocerosate (54). Later work also described one of the substrates of PknD, osmosensory protein A (OprA), to be up-regulated in the presence of increasing extracellular osmolarity and to enable adaptation through modifying peptidoglycan thickness (55,56). Several other enzymes involved in the synthesis of cell wall components are also substrates of PknD, including malonyl-CoA:acyl carrier protein transacylase (FabD) and the ␤-ketoacyl-acyl carrier protein synthases KasA and KasB (39).…”
Section: Discussionmentioning
confidence: 99%